Intervention of the Co-Working Space Program in Shaping the Creative Economy Sector in Bandung City: A Case Study in Gedebage and Batununggal Districts - Lubis, Muhammad Fachry; Nurwati, Nunung; Gunawan, Wahyu (Yayasan Riset dan Pengembangan Intelektual, 2024)
This study aims to examine the interaction between actors, focusing on sources of authority, including political, economic, and normative authority, as well as values and beliefs, which are mobilized in the process of forming, implementing, and sustaining the Co-Working Space program in Bandung City, with case studies in Gedebage and Batununggal Districts. This research employs a qualitative method with a case study approach, and data were collected through purposive sampling and analyzed using NVivo 14 software. The findings reveal that interactions between actors faced challenges such as limited budgets, inconsistent political support, and sectoral egos among government offices, leading to disruptions in program stability and making it difficult for social actors aiming to develop the program to find their working space.